Study on Excitation Forces Generated by Defective Races of Rolling Bearing. (2016) - Shah, Dipen S.; Patel, V.N.
Abstract: The vibrations generated by defective rolling elements bearing play vital role in dynamics of rotating machines. In this paper different approach for simulation and numerical analysis of defective bearing races presented by researchers have been compared and extended for multiple defects. This work has been attempted to demonstrate the way of modelling and simulation of local and distributed defect on inner and outer race of deep groove ball bearing. The bearing defect has been modelled as impulse train force or impact force to cause an additional deflection or excitation of rolling elements. The simulated results have been analysed in time and frequency domain. The characteristics defect frequency and its harmonics and amplitude of vibration response of defective bearing is broadly investigated through simulated results.